Dynamic Oromandibular Reconstructions Using Chimeric Fibular and Gracilis or Vastus Lateralis Free Flaps - Kim, Min Ji; Choi, Jong Woo; Jeong, Woo Shik; Nam, Soon Yuhl; Choi, Seung Ho (Journal of Reconstructive Microsurgery Open, 2020)
Background Despite efforts of head and neck functional reconstruction, anatomic restoration has been used until now. This article describes our experience of using a chimeric free fibular osteocutaneous flap conjoined with a functional muscle free flap, defined as dynamic oromandibular reconstruction.Methods Through a retrospective chart review, four consecutive patients who underwent reconstruction with a total fibular free flap were included. The former two patients underwent reconstruction using a conventional osteocutaneous free fibular flap. The latter two patients had an oromandibular defect after cancer resection and underwent dynamic oromandibular reconstruction with a chimeric free fibular flap conjoined with a gracilis free flap or vastus lateralis muscle free flap.Results In the speech analysis, the dynamic group revealed a satisfactory tongue movement. Protrusion and lateralization were the most different movement changes. The tongue range of motion score was 62.5 in the dynamic group and 25.0 in the control group. On the dynamic magnetic resonance imaging, the contact of the soft palate with the tongue was excellent, and the epiglottis closure during deglutition was complete. In the three-dimensional volumetric analysis of mandibular aesthetic contouring, the dynamic group showed a much smaller difference in hemifacial volume, with a difference of 73.7 mL in the dynamic group and 101.76 mL in the control group.Conclusion This study is a preliminary trial of dynamic oromandibular reconstruction using chimeric free fibular flaps with functional muscle transfer. We demonstrated the possibility of dynamic oromandibular reconstruction, which enhanced more functional aspects in the patients in this study.
Keywords: oromandibular defect; fibular free flap; chimeric flap; functional head and neck reconstruction; dynamic reconstruction